2023
DOI: 10.37774/9789275126653
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Latin America and the Caribbean: Prevalence, Incidence, Impact, and Trends over Time

Abstract: The chapter Dementia in Latin America and the Caribbean: Prevalence, Incidence, Impact, and Trends over Time, is part of the publication series titled “Decade of Healthy Aging: situation and challenges”. This document aims to provide an outline of the current situation in Latin America and the Caribbean in respect of the prevalence and incidence of dementia and its impact on the health status of older people. As dementia is a significant global health problem which also has social and economic impacts this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 58 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Their findings demonstrate that the prevalence of dementia across LatAm is more similar than previously reported, ranging from 6.7% to 12.6% in 2008. 2 , 9 , 10 According to the Global Burden of Disease (GBD), the prevalence of dementia in LatAm in 2019 was the highest in Argentina, Chile, and Uruguay. 2 A recent systematic review and meta‐analyses reported that the prevalence of all‐cause dementia in LatAm is 8% to 10%, with a higher prevalence for women, lower‐educated individuals, and rural residents.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Their findings demonstrate that the prevalence of dementia across LatAm is more similar than previously reported, ranging from 6.7% to 12.6% in 2008. 2 , 9 , 10 According to the Global Burden of Disease (GBD), the prevalence of dementia in LatAm in 2019 was the highest in Argentina, Chile, and Uruguay. 2 A recent systematic review and meta‐analyses reported that the prevalence of all‐cause dementia in LatAm is 8% to 10%, with a higher prevalence for women, lower‐educated individuals, and rural residents.…”
Section: Epidemiologymentioning
confidence: 99%
“… 2 , 9 , 10 According to the Global Burden of Disease (GBD), the prevalence of dementia in LatAm in 2019 was the highest in Argentina, Chile, and Uruguay. 2 A recent systematic review and meta‐analyses reported that the prevalence of all‐cause dementia in LatAm is 8% to 10%, with a higher prevalence for women, lower‐educated individuals, and rural residents. 11 The GBD estimates also suggested a 205% increase in the number of people aged 60 and above in the region between 2010 and 2015, compared to a 102% increase in North America.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations